Dual-pulses and harmonic patterns of a square-wave soliton in passively mode-locked fiber laser. (26th April 2018) - Ma, Wanzhuo; Wang, Tianshu; Su, Qingchao; Zhang, Jing; Jia, Qingsong; Jiang, Huilin
Abstract: We demonstrate a square-wave soliton pulse passively mode-locked fiber laser. The mode-locked pulses are achieved by using a nonlinear amplifying loop mirror. Single-pulse operation at a fundamental repetition rate of 3.2 MHz is obtained. The optical spectrum presents the soliton feature of several sidebands. The pulse duration expands with increasing pump power, but the amplitude hardly varies. Pulse breaking occurs and a stable dual-pulse is obtained with a fixed interval of 48 ns. Harmonic mode-locked states can be achieved when the total pump power is higher than 740 mW. The harmonic pulses can also operate in both single-pulse and dual-pulse states.